A complex of species related to Paradiscogaster glebulae (Digenea: Faustulidae) in chaetodontid fishes (Teleostei: Perciformes) of the Great Barrier Reef. Issue 5 (October 2015) - Diaz, Pablo E.; Bray, Rodney A.; Cutmore, Scott C.; Ward, Selina; Cribb, Thomas H.
Abstract A total of 1523 individuals of 34 species of chaetodontids from the Great Barrier Reef were examined for faustulid trematodes. Specimens resembling Paradiscogaster glebulae Bray, Cribb & Barker, 1994 were found in nine chaetodontid species at three localities. These specimens are shown, on the basis of combined morphological and molecular analyses, to comprise a complex of morphologically similar and partly cryptic species. The complex may comprise as many as six distinct species of which three are resolved here. The true P. glebulae is identified in Chaetodon ornatissimus Cuvier, 1831, Chaetodon aureofasciatus Macleay, 1878, Chaetodon plebeius Cuvier, 1831, Chaetodon rainfordi McCulloch, 1923 and Chaetodon speculum Cuvier, 1831. Two new species are described, Paradiscogaster munozae n. sp. from Heniochus varius (Cuvier, 1829), Heniochus chrysostomus Cuvier, 1831 and Chaetodon citrinellus Cuvier, 1831 and Paradiscogaster melendezi n. sp. from Chaetodon kleinii Bloch, 1790. In terms of morphology the three species differ most clearly in the development of the appendages on the ventral sucker. The three species differ at 3–6 consistent bp of ITS2 rDNA. The host-specificity of the three species differs strikingly. P. melendezi n. sp. infects just one fish species, P. glebulae infects species of only one clade of Chaetodon, and P. munozae n. sp. infects quite unrelated species. The basis of this unusual pattern of host-specificity requires further exploration. Two of the species recognised here, P. glebulae and P. munozae n. sp., showed apparent intra-individual variation in the ITS2 rDNA sequences as demonstrated by clear, replicated double peaks in the electropherograms.